Pengaruh Psychological Factors, Financial Literacy, dan Paylater Misuse terhadap Compulsive Buying pada Pengguna Aplikasi Paylater di Jabodetabek - Namira Nurul Alhakim; Stevia Septiani; Eka Dasra Viana (IPB University, 2023)
The increasing trend of online shopping through e-commerce during the COVID-19 pandemic is also supported by the development of digital payment method, one of which is paylater. Paylater allows consumers to buy now and pay later in monthly installments. Paylater growth in Indonesia can encourage the development of the digital economy and is in line with sustainable development goals (SDGs) number 8, namely increasing inclusive and sustainable economic growth. However, if not controlled, the use of paylaters actually risks triggering compulsive buying behavior and increasing the amount of debt owned by consumers. This research aims to analyze the characteristics of paylater users in Jabodetabek, analyze the influence of psychological factors and financial literacy toward paylater misuse, and analyze the influence of psychological factors, financial literacy, and paylater misuse toward compulsive buying behavior. The sample of this research was 275 respondents of paylater users in Jabodetabek. The research sample was determined using the non-probability sampling method, types convenience sampling and quota sampling. Furthermore, the research results were analyzed using descriptive analysis and Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of this research show that psychological factors, financial literacy, and Paylater misuse hAVE a positive and significant effect on compulsive buying.